Xanthoma tuberosum in homozygous familial hypercholesterolemia - Nagaraja Moorthy; Rajiv Ananthakrishna; Prabhavathi Bhat; Manjunath C Nanjappa (Wolters Kluwer Medknow Publications, 2014)
Familial homozygous hypercholesterolemia is one of the high risk factors that can result in premature coronary arterial disease leading to severe morbidity and premature death in children and young adults. We describe a rare example of extensive xanthoma tuberosum in a case of familial homozygous hypercholesterolemia.